Dysbiosis of the digestive tract after antibiotics treatment - Wawryków, Agata; Korabiusz, Katarzyna; Stecko, Monika; Fabian-Danielewska, Anna; Wilczyńska, Agnieszka; Piątek, Patrycja; Żukowska, Magdalena; Wawryków, Paweł (Journal of Education, Health and Sport, 2019)
A human organism is a great place for living a huge and very diverse microflora. The most colonized seems to be the digestive tract. The balance between the host organism and the microbiome is extremely important. One of the causes of homeostasis disorders may be treatment with antibiotics. During antibiotic therapy, the natural intestinal microbiota is depleted. As a consequence, the risk of uncontrolled development of Clostridium difficile is significantly increased. Intestinal infections due to this pathogenic rote are a serious health problem.